2022
DOI: 10.1021/acsomega.2c03356
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the Isozymes II and IX of Human Carbonic Anhydrase

Abstract: Human carbonic anhydrases (HCAs) are responsible for the pH control and sensing in our body and constitute key components in the central pH paradigm connected to cancer therapeutics. However, little or no molecular level studies are available on the pH-dependent stability and functional dynamics of the known isozymes of HCA. The main objective of this Article is to report the first bench-marking study on the structure and dynamics of the two most efficient isozymes, HCA II and IX, at neutral pH using classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…But the reorganization dynamics at the active site, as presented in Figure c, was significantly affected by the use of a constant-pH condition. For the conformational fluctuation of His-64 side chain in both HCA II and IX-c, the slowest time scale was estimated to be 1 order of magnitude slower than that observed under charge-neutralized condition of conventional MD …”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…But the reorganization dynamics at the active site, as presented in Figure c, was significantly affected by the use of a constant-pH condition. For the conformational fluctuation of His-64 side chain in both HCA II and IX-c, the slowest time scale was estimated to be 1 order of magnitude slower than that observed under charge-neutralized condition of conventional MD …”
Section: Introductionmentioning
confidence: 86%
“…Several short dynamical trajectories should ideally be employed to construct the time-lagged MSM and obtain statistically reliable estimates of free energy and kinetics associated with the transitions of interest. Our earlier work at neutral pH indicated that the rate constants of transition between in and out conformations of His-64 are in the range of 10 8 –10 7 s –1 . Accordingly, we employed a single long CpHMD trajectory of length 1 μs at each pH for each isozyme in the present work.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations